Exploring the challenges in inculcating islamic values among teachers in selected private secondary schools in Klang Valley - Muhammad Amin (Kulliyyah of Education, International Islamic University Malaysia, 2018)
This research intended to explore the challenges in inculcating Islamic values among teachers in selected private secondary schools in the Klang Valley. It aimed to investigate the teachers' perception in inculcating Islamic values in schools. This research also aimed to identify the different challenges faced by teachers based on gender and different schools in inculcating Islamic values. This study used a quantitative research method, which consisted of surveys. Purposive sampling technique was used in this study. The questionnaire was distributed to 145 teachers from three private Islamic secondary schools in the Klang Valley, namely Al-Amin secondary school, International Islamic Secondary (IIS) School and ADNI Islamic Secondary School. A 5-point Likert scale was used to measure the teachers perception about the following: (i) inculcating Islamic values in schools, (ii) approaches used by teachers to inculcate Islamic values in schools, (iii) the challenges faced by teachers in terms of teachers' attitude, (iv) the challenges faced by teachers in terms of school administrative environment and (v) the challenges faced by teachers in terms of teaching materials and instructional aids. Descriptive analysis (frequencies and percentages), Independent Sample t-Test and one-way ANOVA were utilized in this study. The findings showed that most of the teachers in the three schools in the Klang Valley perceived that they are not inculcating Islamic values into their teaching. Meanwhile, most of the teachers faced three different challenges, which were Personal Attitude, School Environment and Teaching Aids. Independent Sample t-Test analysis indicates that there was a statistically significant difference in inculcating Islamic values between gender in all variables on the perceived challenges faced by teachers. However, the result indicated that there are not statistically significant differences based on school in the challenges faced by teachers in inculcating Islamic values. Based on the findings, the researcher suggested that future research should include additional Islamic schools to compare their methods of teaching Islamic studies, which can also include universities.